APLIKASI TEKNOLOGI LASERPUNKTUR DALAM MENINGKATKAN LIBIDO PEJANTAN DOMBA GARUT (Ovis Aries) - herdis, herdis (Badan Pengkajian dan Penerapan Teknologi, 2010)
Libido can be measured by the length of time needed by the ram from teasing ewes to ejaculation. Low libido is one inefficient factor in reproductive process of sheep. The research was carried out to assess the application of laserpuncturetechnology for increasing libido of Garut rams. Results of the research showed that from three ejaculations observed, the ram which was treated with laserpuncture was more responsive in its libido than control. At the first ejaculation, the ram which was treated with laserpuncture needed 20.67 seconds and more responsive than control 35,40 seconds. At the second ejaculation, the laserpuncture treated needed 85 seconds to responsif than control 129,2 seconds. At the third ejaculation, the laserpuncture treated needed 198,6 seconds to responsif than control 209 seconds. In conclusion, laserpuncture at six acupoints in Garut rams can improve libido.